W SPRAWIE WYNAGRADZANIA OSÓB ZARZĄDZAJĄCYCH JEDNOSTKAMI ORGANIZACYJNYMI Z UDZIAŁEM ŚRODKÓW PUBLICZNYCH - Niedbała, Zdzisław (Wydział Prawa i Administracji UAM, 2002)
The article deals with the controversially high remuneration of persons managing State Treasury companies (local governments) and other institutions with public share capital or other public resources. The Author presents the mechanism and political grounds of these phenomena. Much of the observations are devoted to the Act of 3rd March 2000 on remunerating managers of some business entities. The function of this Act was to do away with the discrepancies in the remuneration sphere and to put an end to lavish remuneration of some decision-makers. The desired pay control role can be played in the future also by some court verdicts quoted in this article, including those of the Supreme Court, e.g. of 7th August 2001, dealing with the issue of „fair remuneration”.
REMUNERATION OF MANAGERS IN PUBLIC SHARE CAPITAL ORGANISATIONAL UNITS